On the rise in child and juvenile delinquency in Germany after the end of the COVID-19 pandemic = Zum Anstieg der Kinder- und Jugenddelinquenz nach Ende der COVID-19-Pandemie - Nägel, Christof (Kriminologie - das Online-Journal, 2023)
In 2022, Germany experienced a post-pandemic increase in police-recorded child and juvenile delin-quency that is attracting considerable public attention. To inform this debate, this article summarizes basic criminological knowledge on juvenile delinquency and crime statistics, distinguishes potential causes of a post-pandemic increase in delinquency, and provides a disaggregated analysis of the police crime statistics. Our descriptive analysis reveals that the increase is concentrated in the areas of violent and theft offenses and among 12-to 16-year-olds. Additional simulations suggest that the removal of contact-reducing measures has been followed by large age-typical increases in police-recorded crime among adolescents. However, these normalization effects do not completely account for the observed increases among 12-to 16-year-olds. We argue that temporal displacement effects offer the most parsi-monious explanation forthese excess increases: These cohorts had reduced opportunities to gain the developmentally typical, first criminogenic experiences during the COVID-19 pandemic yearsleading some adolescents to engage in the underlying activities only after the containment measures had been lifted. While such temporal displacement effects are likely to be temporary, our theoretical discussion suggests that the impairment of schools asplaces of social learning, as early warning systems, and as shelters from and detection sites of family violence during the COVID-19 pandemic may lead to addi-tional future increases in juvenile delinquency.